Adhesion Energy of the Fe(BCC)/Magnetite Interface within the DFT Approach. (2015) - Forti, Mariano; Alonso, Paula; Gargano, Pablo; Rubiolo, Gerardo
Abstract: In Industrial applications, the mechanical stability of oxides formed on metallic alloys is a key concern in the determination of component susceptibility to different corrosion mechanisms. In this context, the energy of adhesion is an important parameter. Density functional Theory (DFT) and other atomistic methods are fundamental tools in the determination of this quantity for Metal/Oxide interfaces. In this paper Fe(BCC)/Magnetite interface is assessed within the DFT approach. An Universal Binding Energy Relation (UBER) model is used to calculate the interfacial separation at equilibrium and the adhesion energy.